ANALSIS FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI AKUNTANSI BERBASIS AKRUAL DI PEMERINTAH DAERAH SE-PROVINSI RIAU (Kota Pekanbaru, Kota Dumai, Kabupaten Rokan Hilir) - R. Septian Armel; M. Rasuli; Taufeni Taufik (PEKBIS, 2019)
This study aims to determine the effect of Organizational Commitment on Accrual-Based Accounting Implementation. Furthermore, this study also examines the role ofHuman Resource Competence, Application of Local Government AccountingStandards (SAPD) and Utilization of SIPKD as mediating the relationship betweenOrganizational Commitment to Accrual-Based Accounting Implementation. Thepopulation in this study are all Regional Device Organization (Organisasi PerangkatDaerah - OPD) in Riau Province which are located in Pekanbaru, Dumai and RokanHilir. The sampling method used in this research is purposive sampling, in order toobtain as much as 113 Regional Device Organization as the sample. This studyused primary data by distributing questionnaires to the head of the accountingdepartment and head of sub-section in each OPD. The statistical method used totest the research hypothesis is Structural Equation Model (SEM) based on PartialLeast Square (PLS) with the help of the WarpPLS 6.0 program. The results of thisstudy prove that organizational commitment did not directly influenced theimplementation of accrual-based accounting, but it influenced the implementation ofaccrual-based accounting through human resource competencies, application ofLocal Government Accounting Standards and utilization of SIPKD.